Etude de l’interaction antagoniste entre les bactéries lactiques Et quelques souches pathogènes - BELKHIR, ABDELKADER YAHIA; DOUBAL, NAZIHA (My University, 2024)
Milk bacteria are known for their use in the food industry, in the production of fermented dairy products their ability to inhibit the growth of pathogenic germs may contribute to food security by reducing the risk of contamination by the production of multiple inhibitors. The objective of this work is to investigate the antagonistic power of six dairy strains, which are Lactobacillus plantarum and two strains of lactobacillus fermentum and one strain of Enterococcus faecium after they have revived and confirmed their purity and identity as morphological and biochemical against pathogenic and alteration bacteria. The Barefoot et al method, 1983 used in this research, showed that these lactic bacteria exert an inhibitory effect on pathogenic bacteria with different inhibition diameters from one bacterium to the other. In fact, milk strains have a strong inhibitory effect on the growth of bacteria gram positive (Staphylococcus aureus ATCC 25923) with high diameters between 5 mm et 10 mm and a moderate "stam-specific" effect on Gram-negative species (Pseudomonas aeroginosa ATCC 27853) with diameter 4 mm, 6 mm and 7 mm,9 mm respectively and for E. coli ATSC25922, the diameter is not determined The measurement of the optical density of harmful bacteria shows That after rapid growth, the number of bacteria decreases rapidly after adding the milk bacterial overflow that contained less than one bacteriocine. The study found that lactic acid bacteria have the most sensitive effect on Pseudomonas aeruginosa. The sensitivity of lactic acid bacteria was tested using the antibiotic disk diffusion method. The results showed that the antibacterial effect may vary depending on the characteristics of lactic acid bacteria gram-positive bacteria are more resistant than gram-negative ones, and the diameter of the inhibition zones varies depending on the antibiotic. Differences in resistance and susceptibility can be attributed to the capacity, concentration and mechanism of action of the bacteria.
Keywords: Lactobacillus plantarum; Lactobacillus fermentum; Enterococcus faecium; lactic acid bacteria; pathogenic bacteria; bacteriocin; zones of inhibition; antagonism; Staphylococcus aureus; Pseudomonas aeruginosa; E. coli